Adaptation of Community of Seaweed Cultivation in Disease Attacks and Climate Change in Seriwe Village Jerowaru District - Suparmin Suparmin (Jurnal Biologi Tropis, 2022)
Adjustment to the external environment in carrying out all activities as a result of climate change is a must for every individual, including fishermen in Seriwe village. This study aims: first, to analyze the adaptation of fishermen in the face of climate change and attacks of seaweed disease. Second, analyze the use of leisure time, income, and household expenses of fishermen. The method used in this research is descriptive method with survey technique. The conclusion in this study is that fishing households can adapt to climate change by resting, not going to sea and filling with other activities. If there is an attack of ice-ice disease, fishermen only secure seaweed that is still good. The time used by fishermen for seaweed cultivation increases the working time in a year, which is 90 hours. Fishermen's household income comes from fishing, trading, labor, and seaweed cultivation. Fishermen household expenditures are dominated by food consumption needs.